2015
DOI: 10.1088/0004-637x/806/1/101
|View full text |Cite
|
Sign up to set email alerts
|

LoCuSS: THE SLOW QUENCHING OF STAR FORMATION IN CLUSTER GALAXIES AND THE NEED FOR PRE-PROCESSING

Abstract: We present a study of the spatial distribution and kinematics of star-forming galaxies in 30 massive clusters at 0.15 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

51
400
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(456 citation statements)
references
References 147 publications
51
400
1
4
Order By: Relevance
“…On the latter point, the COS-MOS photometry extends to 8µm, whereas we have observed half of the cluster sample discussed in this article with Spitzer/MIPS at 24µm and with Herschel/PACS and SPIRE at 100 − 500µm (Smith et al 2010), albeit only to a depth corresponding to a bolometric infrared luminosity of LIR ≃ 5 × 10 10 L⊙ at z ≃ 0.2. The spectroscopic completeness of follow-up observations with Hectospec (Fabricant et al 2005) is 96 per cent for objects detected with Spitzer down to 0.5mJy and and ∼ 80 per cent down to i = 20 (Mulroy et al 2014;Haines et al 2015). Clearly these data are not sensitive enough to obtain definitive estimates of the number and redshifts of dusty galaxies that satisfy our faint red optical background galaxy selection.…”
Section: Selection Of Background Galaxiesmentioning
confidence: 84%
See 1 more Smart Citation
“…On the latter point, the COS-MOS photometry extends to 8µm, whereas we have observed half of the cluster sample discussed in this article with Spitzer/MIPS at 24µm and with Herschel/PACS and SPIRE at 100 − 500µm (Smith et al 2010), albeit only to a depth corresponding to a bolometric infrared luminosity of LIR ≃ 5 × 10 10 L⊙ at z ≃ 0.2. The spectroscopic completeness of follow-up observations with Hectospec (Fabricant et al 2005) is 96 per cent for objects detected with Spitzer down to 0.5mJy and and ∼ 80 per cent down to i = 20 (Mulroy et al 2014;Haines et al 2015). Clearly these data are not sensitive enough to obtain definitive estimates of the number and redshifts of dusty galaxies that satisfy our faint red optical background galaxy selection.…”
Section: Selection Of Background Galaxiesmentioning
confidence: 84%
“…However they provide a useful sanity check based on bright galaxies. We select galaxies from the catalogues discussed by Haines et al (2015) at i < 20 that have (V − i) colours that would place them in our red background galaxy catalogues if they were faint enough. We find that ∼ 1 per cent of these bright optically red galaxies are LIRGs, and ∼ 1 per cent of the same bright optically red galaxies are cluster members, and there is no overlap between these two populations.…”
Section: Selection Of Background Galaxiesmentioning
confidence: 99%
“…Bahé et al 2013). To address this, we also show pre-processing results for our 'strict' infall sample (2 < R < 3 R 200 ) which should be less susceptible to backsplash contamination, as many previous studies have shown that the majority of backsplashing galaxies are found within two virial radii (Mamon et al 2004;Mahajan et al 2011;Oman et al 2013;Haines et al 2015). If contamination from backsplash galaxies is low, this field excess should approximate the fraction of galaxies which have been pre-processed prior to infalling onto their present-day group.…”
Section: Galaxy Properties At Large Radiimentioning
confidence: 88%
“…Therefore the fact that our values for the fraction of pre-processed galaxies are consistently smaller than the quoted subhalo fractions is still consistent. Studying the star-forming fractions of cluster galaxies, Haines et al (2015) use a simple toy model in an attempt to reproduce the trend between cluster-centric radius and star-forming fraction. They find that in order to reproduce the observational trend, a 19 per cent decrease in the starforming fraction of cluster galaxies relative to the field is required on top of star formation quenching occuring within the virial radius.…”
Section: Pre-processing Of Infalling Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation